Pengaruh Media Interaktif Terhadap Kemampuan Perkalian pada Aktivitas Siswa Kelas III Sekolah Dasar Negeri Ngagelrejo I/396 - Mufidah, Ellyna Citra; Kusmaharti, Dian (Universitas Muhammadiyah Magelang, 2026)
This study discusses the challenges faced by third-grade elementary school students in understanding multiplication, which are often caused by conventional and monotonous teaching methods that emphasize memorization rather than conceptual understanding. This study aims to investigate the effect of interactive media on students’ multiplication skills and to describe students’ engagement in interactive learning activities. The study was conducted at SDN Ngagel Rejo I/396 Surabaya. The population of this study consisted of third-grade students. Data were collected through observation and pretest–posttest methods. The research instruments included pretest and posttest questions, as well as observation sheets to assess student learning activities. Data analysis was carried out using a t-test, preceded by normality and homogeneity tests. The findings indicate that interactive media has a significant positive effect on students’ multiplication skills and learning engagement, leading to improved learning outcomes of third-grade students at SDN Ngagel Rejo I/396 Surabaya. Therefore, it is recommended that teachers use interactive media as an effective alternative in teaching multiplication to increase students’ interest in both independent and group learning.